20‐2: Novel LCD Frame Frequency Switching Method with Minimized Flicker. Issue 1 (29th May 2019) - Chida, Mitsuru; Kitagawa, Makoto; Fujimoto, Hideki; Nishihara, Yusuke; Hashimoto, Yoshito
Abstract : Variable frame frequency driving such as driving at 120 Hz to 1 Hz is valuable for satisfying both moving picture quality and low power consumption. When driving frequency is switched in LCDs, flickering of images could arise due to fluctuation in the DC voltage component. We report a novel frame frequency switching method for minimizing image flicker after frame frequency switching.